2004
DOI: 10.1016/j.pain.2004.09.011
|View full text |Cite
|
Sign up to set email alerts
|

In vivo recruitment by painful stimuli of AMPA receptor subunits to the plasma membrane of spinal cord neurons

Abstract: The persistent increase in pain sensitivity observed after injury, known as hyperalgesia, depends on synaptic plasticity in the pain pathway, particularly in the spinal cord. Several potential mechanisms have been proposed, including post-synaptic exocytosis of the AMPA subclass of glutamate receptors (AMPA-R), which is known to play a critical role in synaptic plasticity in the hippocampus. AMPA-R trafficking has been described in spinal neurons in culture but it is unknown if it can also occur in spinal neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 34 publications
6
133
0
Order By: Relevance
“…It has been reported that painful stimuli can recruit AMPA receptor GluR1 subunits to neuronal plasma membranes in the lumbar spinal cord (Galan et al, 2004). We next investigated the distribution of AMPA receptor subunits in the ACC after nerve ligation.…”
Section: Membrane Glur1 Expressionmentioning
confidence: 99%
“…It has been reported that painful stimuli can recruit AMPA receptor GluR1 subunits to neuronal plasma membranes in the lumbar spinal cord (Galan et al, 2004). We next investigated the distribution of AMPA receptor subunits in the ACC after nerve ligation.…”
Section: Membrane Glur1 Expressionmentioning
confidence: 99%
“…CaMKII has been implicated in the induction of NMDA receptor-dependent sensitization of neurons in the spinal cord dorsal horn (Fang et al, 2002;Garry et al, 2003;Galan et al, 2004). This central sensitization is a likely mechanism underlying certain forms of hyperalgesia, the enhanced sensation of painful stimuli that may arise after intense noxious stimulation, and is commonly believed to involve LTP-like strengthening of primary afferent transmission that depends on activation of NMDA receptors and CaMKII (Kolaj et CaMKII autophosphorylated at Thr 286/287 (pCaMKII) would be expected at synapses from primary afferent fibers supplying the noxiously stimulated tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Postsynaptic AMPA receptor subunit trafficking, especially GluA1 and GluA2, in the development of synaptic plasticity under pathophysiological conditions may be associated with chronic pain (4, 8 -10). For example, in the anterior cingulate cortex and spinal cord, GluA1 was recruited to the plasma membrane under pain conditions to enhance glutamatergic transmission, leading to a behavioral state of sensitized pain (11)(12)(13). However, the molecular mechanism underlying dynamic distribution of GluA1 after inflammation in the descending pain modulatory circuitry remains unclear.…”
mentioning
confidence: 99%